Podcasting and blogging with GarageBand and iWeb - Williams, Robin, 1953- (Peachpit Press, 2006)
If you've got something to say and want to join the podcasting revolution but don't know how to start, this short and approachable guide from bestselling authors Robin Williams and John Tollett will teach you how to create and distribute podcasts using Apple's easy-to-use audio and Web site tools. Using the Garageband and iWeb tools from Apple's iLife 06 suite of tools, Robin and John show you how to create professional sounding and looking podcasts, including how to add chapter markers, artwork, sound effects, jingles, and musical accompaniment to your podcasts.